Między Rzymem a opozycją antychalcedońską. - Sadurska, Katarzyna (Vox Patrum, 2019)
BETWEEN ROME AND ANTI-CHALCEDONIAN OPPOSITION. THE MAIN DIRECTIONS OF RELIGIOUS POLICY OF EMPEROR LEON I (457-474) (Summary) On the one hand, relations with Rome and the anti-chalcedonian opposition, and on the other, relations with the Patriarch of Constantinople and concern for the orthodoxy of the subjects are the four basic directions of religious policy of Emperor Leon I. The balance of his rule seems to be positive in all four fields of his religious activity. The emperor managed to maintain a good relationship with Pope Leo I „the Great” and his successors, despite the fact that he had to compromise with the opponents of the decisions that were adopted in 451 by the Council of Chalcedon. In turn, the Pope, despite the fact that the 28 canon of this council only granted him the primacy of honor in the hierarchy of patriarchs, was able to cooperate with Constantinople, whose aim was to preserve the unity of the Church. In this way, the emperor Leon I and Pope Leo I proved not only the high personal culture, but also the far-sightedness of their religious policy. However, the important moment in the Emperor’s relations with the Patriarch of Constantinople is the imperial coronation of Leon, in which the Patriarch played a very important role. The emperor also cared for the spiritual life of his